Inklusive Bildung Regionale, nationale und internationale Forschung und Entwicklungslinien - Bešić, Edvina; Holzinger, Andrea; Kopp-Sixt, Silvia; Krammer, Mathias (Studienreihe der Pädagogischen Hochschule Steiermark, 2023)
In addition to contributions from research and development, the focus is on comparative country studies and current issues of digitisation in the context of inclusion. Furthermore, the volume also presents informative short contributions or profiles of current projects. Through this joint national and international The aim of this joint national and international overview of findings and project resources is to strengthen the sustainability of knowledge and ensure its transfer from research to the respective fields of practice.